PORTRAYING THE INFLUENCE OF ENGLISH MASTERY ON SELF-CONFIDENCE OF GROUND HANDLING OFFICERS AT AHMAD YANI INTERNATIONAL AIRPORT - Rahmadani, Pramudya Dwi Putri; Ginusti, Gallis Nawang; Yudianto, Kifni (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
As a ground handling officer who deals directly with passengers, both domestic and international, they should have the ability to speak English confidently. In practice, their English language sometimes undermines their confidence in performing their professional duties. The purpose of this study is to find out whether English proficiency affects the confidence of Ground Handling officers at Ahmad Yani Airport Semarang as well as their English performance in handling foreign passengers. This study used mixed methods, combining quantitative and qualitative data. The data was gathered through the use of questionnaires, interviews, observation, and documentation. Quantitative data analysis employed hypothesis testing and descriptive statistics which were followed by qualitative analysis. The findings of the study indicate the level of English mastery (X) has a significant influence on the self-confidence (Y) of airport ground handlers, proven by the t-test result indicating t-value 4,211 > t-table 2,2024 at the 5% significance level. In general, their English mastery is categorized as “good” However, several issues such as speaking and listening skills as well as vocabulary mastery, contribute to their confidence to perform English in the workplace. They are less confident with their abilities, struggle to communicate their ideas, and rely on coworkers or translation tools.